Increased Incidence of Kawasaki Disease in Taiwan in Recent Years: A 15 Years Nationwide Population-Based Cohort Study - Huang, Ying-Hsien; Lin, Kuan-Miao; Ho, Shu-Chen; Yan, Jia-Huei; Lo, Mao-Hung; Kuo, Ho-Chang (Frontiers in Pediatrics, 2019)
Background: Kawasaki disease (KD) is diagnosed in children suffering from fever for more than five days and five clinical characteristic symptoms. The aim of this article was to research the clinical characteristics among KD children in Taiwan in recent years through a population-based cohort study. Materials and methods: We carried out a nationwide retrospective cohort study by analyzing the data of KD patients (ICD-9-CM code 4461) from Taiwan’s National Health Insurance Research Database (NHIRD) during the period of 1996-2011. Results: Among all the insured children in the NHIRD, insurance claims data were reported for 13,260 patients diagnosed with KD, with 8394 (63.30%) subjects being administered IVIG for treatment. Of the patients diagnosed with KD, 94% were under the age of 5 years old, and the majority of cases occurred in May. Furthermore, the incidence of KD more than doubled (28.58 to 60.08 per 100,000) during this period in Taiwan. Conclusion: We developed a five-based mnemonic device for parents and first-line clinicians to easily use in order to diagnose KD. We also observed an increased incidence of KD in Taiwan during the study period. In addition, we develop a five-based mnemonic device for parents and first-line clinicians in clinical diagnosis of KD can easily remember: Fever> 5 days, 5 clinical criteria, predominantly in children < 5 years of age, and peak seasonal clustering in the 5th month, May (April- June) in Taiwan.